Sources, calculation methods, and reduction strategies for GHG emissions at ports: current status and future trends - Shen, Jinxing; Gao, Wenlong; Lu, Jingwei; Li, Fengjiang; Feng, Xuejun (Frontiers in Marine Science, 2025)
Greenhouse gas (GHG) emissions from ports have gained increasing attention due to their significant impact on climate change. Nevertheless, the existing research in this domain remains fragmented, with limited generalizable findings. To address this gap, an integrative framework is proposed in this study to systematically review the literature and identify future research directions. Using the Web of Science database, a bibliometric analysis of 230 documents and an in-depth review of 68 studies are conducted, focusing on emission sources, emission calculations, and abatement technologies. Key findings can be drawn as follows: (1) Research on port-related GHG emissions has expanded rapidly since the Paris Agreement, but international collaboration and institutional coordination remain insufficient, hindering the development of comprehensive solutions. (2) Inconsistent classification of GHG emission sources across studies leads to biases and limits comparability. Reclassifying emissions based on equipment operation locations could improve both accuracy and cross-study alignment. (3) Activity-based approaches are the primary methods for emissions assessment but heavily rely on static emission factor datasets, particularly for container ports. Expanding these datasets for diverse port types, updating localized factors in real-time, and integrating alternative energy sources can enhance adaptability and accuracy. (4) Current mitigation strategies focus on technological innovations, energy substitution, and operational optimization. However, limitations such as high implementation costs, slow commercialization, and insufficient policy support continue to impede progress. To achieve zero-carbon port operations, future research should prioritize the integration of technical innovations with economic and policy frameworks. A multidisciplinary approach is essential for overcoming current barriers and promoting sustainable practices in port management.